KOMUNIKASI PERSUASIF BADAN PENASEHATAN PEMBINAAN DAN PELESTARIAN PERKAWINAN PADA PASANGAN YANG INGIN BERCERAI DI KOTA PEKANBARU - Wahyu Mharfin; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Counselling Agency for Development and Preservation Agency Marriage is engaged in the field of marriage counseling and divorce rate reduction program in order to support the Department of Religion. Many couples who come to resolve domestic problems. Proven during 2013, Development and Preservation Advisory Board Marital received about 100 reports of married couples who want to resolve the problem. Among the 30 couples report the problem to continue the Islamic Court. The purpose of this study was to determine how the process of persuasive communication and persuasive communication techniques used in the Advisory Board of the Development and Preservation of Marriage. This study uses descriptive qualitative research with data collection techniques of observation, interviews and documentation. This study was carried out in the Development and Preservation Advisory Board Marriage Pekanbaru. The object of this research that Persuasive Communication Advisory Board Development and Preservation of Marriage (BP4) in couples seeking divorce in Pekanbaru with research subjects who meet the research needs of as many as three people consisting of Staff Development and Preservation Advisory Board marriage and couples. The study lasted for seven months ie from September 2014 until March 2015. The results showed that the process of persuasive communication Development and Preservation Advisory Board marriage on couples who want to divorce them see the persuader. Persuader have an understanding of marriage according to Islam. The media used by the persuader face-to-face and mediated namely using a mobile phone. Effect happens to persuade accordance with what is expected persuader that couples get solutions and do not lead to a divorce. Although the pair remains divorced, it is the best solution for each partner. Persuasive Communication Process Development and Preservation Advisory Board Marital use persuasive communication techniques to convey a message. The message is based on jurisprudence munakahat or marriage according to Islamic law. Persuasive communication techniques used Development and Preservation Advisory Board marriage of husband and wife to face the technique of simulated disinterest, transfers, the swap technique and technique of irritation. Keyword :Persuasive Communication, Persuasive Communication Technique, Couples